Reflection of the Semipalatinsk tragedy in Kazakh poetry (Based on the poetry of U. Esdaulet, T. Abdykakimov, B. Zhakyp) - Musinova, Г.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The article is devoted to the reflection of the tragedy of Semipalatinsk in Kazakh poetry. The poem «Zaman-ai» by the poet U. Esdaulet, the poem «Kara Dala» by the poet T. Abdykakimov and the poem «Zhan Dauysy» by the poet, scientist B. Zhakyp reflect the tragedy of the Semipalatinsk test site. The tragic fate of nature and humanity under the influence of the Semipalatinsk nuclear test site is very vividly and truthfully described in artistic language. Special attention is paid to the poetic works dedicated to the tragedy of Semipalatinsk. The poetic works of Ulugbek Esdaulet, Tynyshtyk Abdykakimov, Baurzhan Zhakyp about the tragedy of Semipalatinsk are one of the most valuable spiritual treasures in the history of Kazakh literature